ПЛАНИРОВАНИЕ ДИСКРЕТНОГО ПРОИЗВОДСТВА В УСЛОВИЯХ НЕПОЛНОТЫ ИНФОРМАЦИИ - Суханцев, Сергей Станиславович; Гитман, Михаил Борисович (Вестник ИжГТУ имени М.Т. Калашникова, 2014)
The solution of a problem of planning and replanning of discrete production by the fuzzy sets theory is submitted. This problem is a two-criterial optimization problem, where as criteria the costs of production and personnel opinion are considered. The solution of a problem of planning and replanning of discrete production by the fuzzy sets theory is submitted. This problem is a two-criteria optimization problem, where criteria of the costs of production and personnel opinion are considered.